Protocolo de investigação e manejo do AVC isquêmico neonatal - Nicolas Ramos; Gustavo Barbosa David; Simone Cristina Stadnick; Stephanie Ribeiro Raitez (Residência Pediátrica)
OBJECTIVE: To describe the condition, the management of the case and its clinical manifestations in order to alert healthcare professionals regarding the importance of early diagnosis of Neonatal Arterial Ischemic Stroke (NAIS). CASE REPORT: Male newborn, delivered at a tertiary hospital in the state of Santa Catarina, Brazil, via cesarean section at an early term, with no reported complications. Upon birth, the baby presented with hypotonia, hypoactivity, and weak crying. Subsequently, bradycardia and the need for positive pressure ventilation and hypoglycemia were observed. Within the first hours of life, the baby exhibited tremors in the upper limbs upon stimulation. Laboratory tests did not clarify the situation, therefore blood cultures and cerebrospinal fluid samples were requested. At 24 hours of life, persistent tremors and drooping of the right side of the mouth were noted, raising suspicion of convulsive seizures. Management included phenobarbital to control the symptoms. A head computed tomography revealed hypodensity in the right hemisphere, suggestive of hypoxic-ischemic injury. A brain computed tomography angiography did not reveal any signs. Following discussions with the neuropediatrician and neurosurgeons, the diagnosis of NAIS was established. In the subsequent days, the patient was closely monitored and discharged with instructions on the 35th day of life. DISCUSSION: NAIS is a prevalent condition among newborns. Howerer, diagnosis rates in Brazil are lagging behind due to the nonspecific clinical manifestations and the insufficient attention to the topic within the medical community. In this context, individuals affected by NAIS endure lifelong consequences.